Valor biológico da dieta à base de okara e os seus efeitos sobre o perfil hormonal e metabólico em ratos adultos submetidos à restrição protéica na vida intra-uterina e lactação e recuperados após o desmame - Lemes, Simone Ferreira (2012)
We assessed the biological value of an okara diet and its effects on the hormonal and metabolic profile of rats submitted to protein restriction during intra-uterine life and lactation and recovered after weaning. Male rats from mothers fed either 17% or 6% protein during pregnancy and lactation were maintained on 17% casein (CC, LC), 17% okara (CO, LO) or 6% casein (LL) diets over 60 days. The nutritional quality of the okara protein was similar to that of casein. Total and relative energy intake was lower in LO and CO rats, but body weight did not differ among the groups. The absolute and relative weights of epididymal and retroperitoneal fat deposits were lower in LO, LC and CC groups than in the CO group. In the fed state, serum glucose and insulin concentrations and the insulin:glucose ratio were lower in LO, CO and LC rats than in CC rats. Serum glucagon concentrations did not differ among groups, but the glucagon:insulin ratio was higher in LO, CO and LC rats than in CC rats. Liver and muscle glycogen contents were lower in LO and CO rats than in LC and CC rats. Liver fat content was higher in the LO and CO rats than in LC and CC rats. However, liver fat content in LO rats was lower than in LL rats. The glucose area under the curve during glucose and pyruvate tolerance tests was lower in LO and CO rats than in LC and CC rats. Thus, okara diets were effective in the nutritional recovery of early malnourished rats and also prevented the development of obesity, hepatic steatosis and glucose intolerance.